Proceedings of the 28th Annual ACM Symposium on Applied Computing 2013
DOI: 10.1145/2480362.2480579
|View full text |Cite
|
Sign up to set email alerts
|

Energy consumption estimation of virtual machines

Abstract: Energy consumption of IT increased continously during the last decades. Numerous works have been accomplished for improving energy efficiency of hardware whereas software energy efficiency has been ignoried for a long time. This contribution presents a novel approach for estimating energy consumption of applications in different execution environments. The system is the basis for automatic optimization of software execution in an energy-efficient way by finding the best-suiting host computer. Thus, it opens no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(44 citation statements)
references
References 8 publications
0
43
0
1
Order By: Relevance
“…The literature usually assumes power consumption as linear function of load [7]. In [14] we show that a linear model is not sufficient in current energy-efficient server architectures as the implemented energy-reduction mechanisms often result in a non-linear dependency of energy consumption by load. Exemplarily we showed that for a 6 core AMD Phenom II X6 1090T and an 8 core Intel Xeon CPU E5620 [14].…”
Section: ) Consumption Estimationmentioning
confidence: 95%
See 2 more Smart Citations
“…The literature usually assumes power consumption as linear function of load [7]. In [14] we show that a linear model is not sufficient in current energy-efficient server architectures as the implemented energy-reduction mechanisms often result in a non-linear dependency of energy consumption by load. Exemplarily we showed that for a 6 core AMD Phenom II X6 1090T and an 8 core Intel Xeon CPU E5620 [14].…”
Section: ) Consumption Estimationmentioning
confidence: 95%
“…In [14] we show that a linear model is not sufficient in current energy-efficient server architectures as the implemented energy-reduction mechanisms often result in a non-linear dependency of energy consumption by load. Exemplarily we showed that for a 6 core AMD Phenom II X6 1090T and an 8 core Intel Xeon CPU E5620 [14]. Thus, our energy model approximates the energy consumption by polynomial regression (method of least squares) with varying degrees of the polynomial function.…”
Section: ) Consumption Estimationmentioning
confidence: 97%
See 1 more Smart Citation
“…We use a power consumption model based on the parameters introduced in [16] and [24] to model the consumption of stand-alone BBUs placed with a RRH on a Distributed RAN (DRAN) node, cloud and fog nodes that consolidates vBBU processing, vBBUs instantiated on processing nodes and LC used to terminate traffic from a VPON. The power consumed to maintain a stand alone BBU at the RRH is equal to 600 W, and this consumption is related to the BBU itself.…”
Section: Power Consumption Modelmentioning
confidence: 99%
“…Krishnan in [30] used not only CPU utilization, but also memory consumption. Versick in [35] proposes a polynomial model. In this model network interface card (NIC) power consumption and hard disk power consumption is measured.…”
Section: Vm Power Consumptionmentioning
confidence: 99%